9 +16 -1 = 24
= (9-6) x (7+1)
24
To equal 24 using the numbers 1, 1, 9, and 6, you can use the following mathematical expression: (9 - 1) x (6 + 1) = 8 x 7 = 56. Then, take the square root of 56 to get 24.
One way is: (6*4)-3+2+1 = 24
6*5*1-6
9 +16 -1 = 24
= (9-6) x (7+1)
24
The only way I know how to do it is 12+13=25, 6 divided by 6=1, and 25-1=24
To make 24 using 1, 3, 4, and 6, you can use the following mathematical operations: (6 / (1 - (3/4))). This equation breaks down as follows: first, divide 6 by (1 - (3/4)), which simplifies to 6 / (1 - 0.75) = 6 / 0.25 = 24. Therefore, using these numbers and operations, you can make 24.
To equal 24 using the numbers 1, 1, 9, and 6, you can use the following mathematical expression: (9 - 1) x (6 + 1) = 8 x 7 = 56. Then, take the square root of 56 to get 24.
One way is: (6*4)-3+2+1 = 24
6+6+6+6=24 4+4+4+4+4+4=24 6+6+4+4+4=24 6+6+6+4+1=24
By using: (3*6)+(3*2) = 24
24 = 9 + 9 + 6
Here is one way: (5 + 1)*(8 - 4) = 6 * 4 = 24